Manufacturing, Characterization, and Activity Testing of Edible Film from Sweet Orange Skin Pectin (Citrus sinensis l.) with the Addition of Tapioca Flour and Glycerine as Plastic (Journal of Chemical Natural Resources, 2020)
Preparation of edible films from the peel of sweet oranges (Citrus sinensis L.) has been done by the addition of tapioca starch and glycerol as plasticizers. Edible films are made by mixing pectin and starch with 0.6; 1.2; 1.8; 2.4; dan 3.0 g variations, by adding glycerin with a fixed composition of 1 mL. Once homogeneous, printed on an acrylic plate and dried at 35 to 45ÂºC temperature in an oven for 2 days. Characterization of edible film physically by measuring thickness, tensile strength, and elongation. From the characterization obtained thickness 0.125 mm, tensile strength 0.32 kgF / mm2 and elongation 10.2 %. Analysis of nutrient content of edible film produces 75.583% carbohydrate content, 1.707 % protein content, 0.725 % fat content, 21.2 % moisture content, and 0,785 % ash content. FTIR (Fourier Transform Infrared) spectrum analysis with absorption at 3603.03 cm-1 range showed hydroxyl group (OH), absorption at 2985.81 cm-1 and 2870,08 cm-1 ranges showed alkane group (CH), absorption at 1759.08 cm-1 range showed (C=O) group of carboxyl acid and absorption at 1168,86 cm-1, 1126.43 cm-1 dan 1064.71 cm-1 ranges showed (C-O) groups of carboxyl acid. Morphology test of SEM (Scanning Electron Microscopy) produces edible film is a flat, tight, and compatible surface structure. Antioxidant activities tests with the DPPH method produce an IC50 value of 49.667 mg/L. Antibacterial activities tests with Kirby Bauer method produce positive tests in Staphylococcus aureus bacterial with antimicrobial index 0.374 and Escherichia coli bacterial 0.337 and Standart count Plate test in the edible film as layer cake wrapping is obtained the colony numbers less than layer cake without edible film wrapping.